Demokrasi Mahasiswa Universitas PGRI Palembang yang Dilaksanakan oleh Organisasi Mahasiswa (ORMAWA) - Boby Agus Yusmiono (Jurnal Studi Sosial dan Politik, 2018)
Intention of this research is to understanding the role of PGRI university Palembang to elevate democracy to its student. This method research use the quantitative research procedure [is] way of measurement by using traditional Scale Guttman model ( cross sectional) in the form of number, percentage. The result of research show that the opinion from interview by 30 are manager Ormawa in environment of PGRI university Palembang, that is from result interview shall be as follows ( 1) indicator of college student knowledge to knowledge democratize that is equal to 64,75%, in meaning enough its Knowledge in democratizing. ( 2) Indicator of student involvement in campus democracy that is equal to 39,40%, meaning students are do not got mixed up with by a campus democracy in PGRI university Palembang. ( 3) Assessment Indicator of equal to 21,67% meaning campus democracy in PGRI university Palembang assessed is not effective and efficient. ( 4) indicator of freedom Expectation democratize equal to 68,20%, meaning Ormawa hope to own the role and freedom creativity in democratizing PGRI university Palembang.